ANALISIS PERBANDINGAN KINERJA KEUANGAN PADA PT BAKRIELAND DEVELOPMENT TBK DENGAN PT WIJAYA KARYA PERSERO (TBK) PERIODE 2019 – 2023 - Zeze Zakaria Hamzah; Muchammad Hamdani; Muhlis; Dwita Aulia Ramadhanty (Economicus : Jurnal Ekonomi dan Manajemen, 2025)
This study aims to identify and analysing the financial performance of PT Bakrieland Development Tbk (stock code ELTY) and PT Wijaya Karya (Persero) Tbk (stock code WIKA) for the period 2019-2023 based on liquidity ratios, solvency ratios, profitability ratios, and activity ratios in the years 2019-2023. Data analysis was conducted by calculating financial ratios, analysing, comparing, and performing verification. The results of this study show that: (1) The liquidity ratio of ELTY increased, which indicates that the company's financial performance is in good condition, whereas the liquidity ratio of WIKA decreased, indicating that the company's financial performance is less favourable; (2) The solvency ratio of ELTY decreased, indicating that the company's financial performance is in good condition, whereas the solvency ratio of WIKA increased, indicating that the company's financial performance is less favourable; (3) The activity ratio of ELTY increased, which means the company's financial performance is currently good, unlike WIKA's activity ratio, which decreased, indicating that the company's financial performance is currently less favourable; and (4) The profitability ratios of both ELTY and WIKA show similarities, as both decreased, indicating that the company's financial performance is currently less favourable.